Bromination of guaiacol and syringol using ionic liquids to obtain bromides. Issue 6 (24th August 2015) - Sequeiros, Ane; Serrano, Luis; Labidi, Jalel
Abstract: BACKGROUND: An understanding of the bromination reaction with guaiacol and syringol allows value added products to be obtained from the lignin depolymerized oil. RESULTS: N‐bromosuccinimide (NBS) and the ionic liquid [Bmim]Br were combined to brominate guaiacol (G) and syringol (S) at room temperature (25 °C). The first step was to bromine guaiacol and syringol separately for a better understanding of the process. The mixture of G and S was brominated with two different solvents diethyl ether (DEE) and ethyl acetate (EtAc) during the L‐L extraction to observe variations in the process and the conversion. The results were analyzed by GC‐MS and 13 C NMR. The mass spectra showed the formation of isomers of p ‐BrG and p ‐BrS. The two solvents gave similar results. However, even though the conversions of G and S were higher with DEE (XG 67.19% and XS 71.86%) than with EtAc (XG 49.62% and XS 59.90%), EtAc (ΣXBrG 29.94% and ΣXBrS 28.29%) extracted in proportion more of the desired products than DEE (ΣXBrG 24.22% and ΣXBrS 34.86%). CONCLUSIONS: The results of the first experiments showed the formation of isomers of p ‐BrS and p ‐BrG. The second results showed that EtAc was able to extract more products than DEE. In conclusion, EtAc was the better solvent for the bromination reaction with the advantage of easy handling and recyclability. © 2015 Society of Chemical Industry